Slovenian Traditional Music and the Media: A Study of Early Gramophone Records - Kunej, Drago (Interdisciplinary Studies in Musicology, 2022)
The article focuses on early commercial recorded music on gramophone records and analyses the beginnings of commercialisation and popularisation of Slovenian traditional music through new technical advances and the emergence of the gramophone industry. It is based on an analysis of a large amount of material, collected in the Digital Collection of Gramophone Records at the Institute of Ethnomusicology ZRC SAZU in Ljubljana, Slovenia, as well as on various written sources and metadata. Slovenian material on early gramophone records, known predominantly as 78 rpm records or shellac records, was being recorded for a good fifty years, from the very first recordings in the early 20th century to the end of the era of these gramophone records in the mid-1950s. Due to the characteristics of the mass medium, the traditional music, which can frequently be found on the early Slovenian gramophone recordings, moved outside its traditional and local bounds and becoming part of the culture industry and marketing. The article presents the characteristics of this medium and the recordings made on it, and shows how such recordings can help to shed new light on various aspects of traditional music. It reveals that folk tradition was adapted, popularised and transmitted for different types of audiences and raises the question of commercialism and its influence on the further development of traditional musical creativity, popularisation and contribution to the development of new popular-music genres.